Markers of Primary Chemoresistance of Epithelial Ascites Cells in Patients with Ovarian Cancer Guidelines for Practitioners - D. R. Dolgova; T. P. Gening; T. V. Abakumova; S. O. Gening; I. I. Antoneeva; A. B. Pescov; A. Yu. Fedotova (Антибиотики и Химиотерапия)
Determined the primary chemoresistance markers (expression of genes ERCC1, TOP2a and ABCB1) in epithelial cells of ascites 32 primary patients with verified ovarian cancer using RT-PCR. After standard chemotherapy by the AR scheme (cisplatin+doxoru-bicin), the relapse-free survival of patients was assessed by Kaplan-Mayer. Patients with early (up to 6 months) and late (more than 6 months) relapse were isolated. As a result of the conducted studies it was established that early relapse occurred in 67% of the examined patients (the relapse-free period was 88.7+13.3 days). At the same time, in the groups with increased expression, the relapse-free period did not differ significantly, there were early relapses. The use of the Cochrane Q-test has allowed to establish that the reduced levels of ERCC1 and ABCB1, the proportion of survivors is to 72.7% (p